The Expression of NOX From Synthetic Promoters Reveals an Important Role of the Redox Status in Regulating Secondary Metabolism of Saccharopolyspora erythraea - Li, Xiaobo; Chu, Ju; Jensen, Peter R. (Frontiers in Bioengineering and Biotechnology, 2020)
Redox cofactors play a pivotal role in primary cellular metabolism, whereas the clear link between redox status and secondary metabolism is still vague. In this study we investigated effects of redox perturbation on the production of erythromycin in Saccharopolyspora erythraea by expressing the water-forming NADH oxidase (NOX) from Streptococcus pneumonia at different levels with synthetic promoters. The expression of NOX reduced the intracellular [NADH]/[NAD+] ratio significantly in S. erythraea which resulted in an increased production of erythromycin by 19∼29% and this increment rose to 60% as more oxygen was supplied. In contrast, the lower redox ratio resulted in a decreased production of another secondary metabolite, the reddish pigment 7-O-rahmnosyl flaviolin. The metabolic shifts of secondary metabolism results in a higher NADH availability which compensates for its oxidization via NOX. The expression of the erythromycin biosynthesis gene cluster (BGC) in the NOX-expression strains was upregulated as the activity of diguanylate cyclase was inhibited moderately by NADH. This study also suggested that lower intracellular [NADH]/[NAD+] ratio benefits the biosynthesis of erythromycin by potentially affecting the biosynthesis of the secondary messenger, bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP), which may stimulate the positive regulation of erythromycin BGC via BldD. The present work provides a basis for future cofactor manipulation in S. erythraea to improve the industrial production of erythromycin.